2019
DOI: 10.21203/rs.2.10856/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Completion rate of Physician Orders for Life-Sustaining Treatment for patients with metastatic or recurrent cancer: A preliminary, cross-sectional study

Abstract: Background: “End of life” is a difficult topic of conversation in East Asian cultures, even among patients and doctors who share a good rapport. In 2016, the Hospice, Palliative Care, and Life-Sustaining Treatment Decision-Making Act, which took the form of “Physician Orders for Life-Sustaining Treatment,” was introduced in South Korea. This study was conducted to investigate the completion rate of Physician Orders for Life-Sustaining Treatment in patients with advanced cancer on the active recommendation of p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…Studies reported that patients’ beliefs about the benefits of advance care planning were important motivators of their engagement in it; such benefits include the belief that advance care planning promoted autonomy, 25,28,35,37,42,44,5658 enabled a comfortable end-of-life, 28,37,40,57,58 avoided burdening family members, 25,28,35,37,44,57 and facilitated shared understanding with family members. 37,42,56 Conversely, five groups of patients would be less likely to engage in advance care planning: (a) those who believed that it was not beneficial 43,56 ; (b) those who believed that engaging in it might cause conflict between their family members or distress to them 41,42,44,48,50,55,58 or to themselves 29,30,33,41,42,55 ; (c) those who believed that discussing death would bring bad luck 30,50,58 ; (d) those who believed that signing the advance care planning document would lead to substandard care 30 ; and (e) those who were not sure that it would guarantee their wishes were respected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies reported that patients’ beliefs about the benefits of advance care planning were important motivators of their engagement in it; such benefits include the belief that advance care planning promoted autonomy, 25,28,35,37,42,44,5658 enabled a comfortable end-of-life, 28,37,40,57,58 avoided burdening family members, 25,28,35,37,44,57 and facilitated shared understanding with family members. 37,42,56 Conversely, five groups of patients would be less likely to engage in advance care planning: (a) those who believed that it was not beneficial 43,56 ; (b) those who believed that engaging in it might cause conflict between their family members or distress to them 41,42,44,48,50,55,58 or to themselves 29,30,33,41,42,55 ; (c) those who believed that discussing death would bring bad luck 30,50,58 ; (d) those who believed that signing the advance care planning document would lead to substandard care 30 ; and (e) those who were not sure that it would guarantee their wishes were respected.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, 36 were included (Figure 2), 22 of which had used quantitative methods, 10 of which had used qualitative methods, and 4 of which had used mixed methods (Table 1 and Supplemental Appendix 2). A majority of the studies (N = 25) had been conducted in high-income countries 22 : Japan, [23][24][25][26] South Korea, 24,[27][28][29][30][31][32][33][34][35] Hong Kong, [36][37][38][39][40][41] Singapore, [42][43][44] and Taiwan. [45][46][47][48][49][50] The term advance care planning was used in 15 studies, most of which had been published in the last decade.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study on intensive care unit doctors in Asia reported that among the factors that these doctors considered to be important in making LSTrelated decisions, the needs of the family accounted for 77.9%; it was only surpassed by the factors patient's intention (84.1%) and long-term quality of life [3]. It is well-established fact that the physician's perception of the intention of the family and the preference of the patient may sometimes be different than the patient's original intention [1,20,21]. Personal characteristics or experience of the physician could also influence LST-related decisions, which inherently presents the risk of a decision being made contrary to the patient's intention [11].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that one in three US adults files any type of advance statement on LST [17], longterm policies for increasing the completion rate of advance statement on LST among adults aged ≥19 years are needed in Asia, including South Korea [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%